Dari Etika Domestik ke Etika Kekuasaan: Membaca Qiwa>mah dalam QS. al-Nisa>‘/4:34 - Rasyid, Muhammad Dirman; Reskiani, Anugrah; Nur Murdan, Muhammad; Makmur (PAPPASANG, 2025)
This article examines the concept of qiwa>mah in QS. al-Nisa>‘/4:34 by going beyond interpretations that limit it to domestic ethics in husband-wife relationships. Through a qualitative approach based on literature study and semantic-relational analysis, this article shows that qiwa>mah not only functions as a normative status or legitimization of gender hierarchy, but also as an ethical function that arises from certain excess (fad}l) and is manifested through concrete responsibility (anfaq). By placing the family as the smallest social unit, QS. al-Nisa>‘/4:34 can be read as a pedagogical medium of the Qur’an to explain the principles of managing asymmetrical relationships ethically. This reading places qiwa>mah as a framework of the ethics of power that emphasizes protection, justice, and the prevention of injustice, and is relevant to broader social and political relations. Artikel ini mengkaji konsep qiwa>mah dalam QS. al-Nisa>‘/4:34 dengan melampaui pembacaan yang membatasinya sebagai etika domestik dalam relasi suami-istri. Melalui pendekatan kualitatif berbasis studi kepustakaan dan analisis semantik-relasional, artikel ini menunjukkan bahwa qiwa>mah tidak hanya berfungsi sebagai status normatif atau legitimasi hierarki gender, melainkan juga sebagai fungsi etis yang lahir dari kelebihan (fad}l) tertentu dan diwujudkan melalui tanggung jawab konkret (anfaq). Dengan menempatkan keluarga sebagai unit sosial terkecil, QS. al-Nisa>‘/4:34 dapat dibaca sebagai medium pedagogis Al-Qur’an untuk menjelaskan prinsip pengelolaan relasi asimetris secara etis. Pembacaan ini menempatkan qiwa>mah sebagai kerangka etika kekuasaan yang menekankan perlindungan, keadilan, dan pencegahan kezaliman, serta relevan bagi relasi sosial dan politik yang lebih luas